Identifikasi Mineral Target Serpentin dan Analisis Kelurusan Citra Digital Elevation Model di Daerah Routa, Kabupaten Konawe - Setiadi, Imam Noor; Kurniadi, Adelia; Sudirman, Sudirman (Journal of Geographical Sciences and Education, 2025)
Geological mapping in mineral exploration plays an important role in finding economical, fast, and efficient mineral resources. Remote sensing techniques with Landsat 8 optical imagery are used for the identification of serpentine minerals to assist in the interpretation of the potential for laterite mineral deposits. The Digital Elevation Model data is used to analyze the lineaments and principal stresses using the multiple inverse method. Identification of serpentine minerals can help in narrowing the target area of ​​exploration and interpretation of the presence of laterite nickel deposits. Serpentine minerals which are often associated with ultramafic rocks are alteration products of olivine which is a nickel carrier found in the southern part. Meanwhile, the direction of the main stresses in the research area is relatively northeast - southwest and northwest - southeast with the formation of fault types in the form of sinistral shear faults and oblique faults. This study can minimize land clearing and detail the target area at the exploration stage.